On the decay of exponential type for the solutions in a dipolar elastic body. Issue 1 (1st January 2020) - Marin, Marin; Ellahi, Rahmat; Vlase, Sorin; Bhatti, M. M.
Abstract : Our study is concerned with a generalization of the principle of Saint-Venant in the context of the theory of elastic bodies with a dipolar structure. It is an extension of the form of this principle proposed by Toupin in the case of classical linear elasticity. We consider a straight cylinder which is occupied by an dipolar elastic body that is only loaded at one end and our main finding proves that the internal energy in a portion of this cylinder, that is located at a given distance regarding the end that is loaded, is exponentially decreasing, regarding the respective distance.